2019
DOI: 10.3389/fpls.2019.00348
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of a Prolyl 4 Hydroxylase Results in Delayed Abscission of Overripe Tomato Fruits

Abstract: The tomato pedicel abscission zone (AZ) is considered a model system for flower and fruit abscission development, activation, and progression. O-glycosylated proteins such as the Arabidopsis IDA (INFLORESCENCE DEFICIENT IN ABSCISSION) peptide and Arabinogalactan proteins (AGPs) which undergo proline hydroxylation were demonstrated to participate in abscission regulation. Considering that the frequency of occurrence of proline hydroxylation might determine the structure as well the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The first gene, Solyc01g017220, coding for an ATP synthase epsilon chain, is reported to be involved in drought stress responses [ 47 ]. The genes Solyc02g070280 , which codes for a protein involved in the transport of amino acids during the pedicel abscission [ 48 ], and Solyc07g053640 , which codes for an arabinogalactan-protein that could be involved in abscission events [ 49 ], might impact on FS. This is a yield-related trait highly affected by high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The first gene, Solyc01g017220, coding for an ATP synthase epsilon chain, is reported to be involved in drought stress responses [ 47 ]. The genes Solyc02g070280 , which codes for a protein involved in the transport of amino acids during the pedicel abscission [ 48 ], and Solyc07g053640 , which codes for an arabinogalactan-protein that could be involved in abscission events [ 49 ], might impact on FS. This is a yield-related trait highly affected by high temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic character of P4Hs mutations reveals also the functional importance of AGPs with respect to growth and development. Genetic mutant analysis of tomato P4Hs transgenic lines indicates the importance of the Agp’s content and possibly their glycan chains for the differentiation and development of fruit abscission fracture plane as well as the progression of the natural abscission process 18 . For the first time in tomato, alterations in the function of post-translational modification such as proline hydroxylation revealed the significance of AGPs glycosylation in the differentiation of fruit abscission zone 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic studies of abscission zones showed anatomical alterations in mutant fruit, i.e. variations in the numbers of parenchymal layers indicating cells detained in an undifferentiated stage as well as disruption in lignin deposition 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations